สภาพและความต้องการพัฒนาห้องเรียนกลับด้านบนคลาวด์โดยใช้การเรียนแบบปัญหาเป็นฐานในสังคม พหุวัฒนธรรมเพื่อส่งเสริมการคิดอย่างมีวิจารณญาณ (Assessment of the Current State and Needs Related to Development of a Cloud-based Flipped Classroom Using Problem-based) - ไสยสิทธิ์ พิชญ์สินี; กรณีกิจ ประกอบ; เกาไศยาภรณ์ โอภาส (บรรณศาสตร์ มศว, 2019)
บทคัดย่อ การศึกษานี้มีวัตถุประสงค์เพื่อศึกษาสภาพและความต้องการในการพัฒนาห้องเรียนกลับด้านบนคลาวด์โดยใช้การเรียนแบบปัญหาเป็นฐานในสังคมพหุวัฒนธรรมเพื่อส่งเสริมการคิดอย่างมีวิจารณญาณ โดยใช้แบบสอบถาม กลุ่มตัวอย่างที่ใช้ในการวิจัย คือ นิสิตนักศึกษาระดับปริญญาตรี สถาบันอุดมศึกษาของรัฐ ในภาคกลางและภาคใต้ จำนวน 445 คน สุ่มตัวอย่างด้วยเทคนิควิธีการแบบก้อนหิมะ ใช้วิธีวิจัยเชิงปริมาณ เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถาม ผลการวิจัยพบว่า นิสิตนักศึกษาระดับปริญญาตรีส่วนใหญ่มีระดับความรู้และทักษะในการใช้งานเทคโนโลยีสารสนเทศในระดับปานกลาง มีการเข้าถึงอินเทอร์เน็ตด้วยการเชื่อมต่อผ่านอุปกรณ์สมาร์ตโฟนมากที่สุด มีความต้องการพัฒนาห้องเรียนกลับด้านบนคลาวด์ ได้แก่ การวัดผลการเรียนรู้ก่อนและหลังเรียน ผู้สอนที่เอาใจใส่ ให้คำชมเชยและเสริมแรงในการเรียน การเน้นกิจกรรมการเรียนรู้ที่เริ่มต้นโดยปัญหาเพื่อให้ผู้เรียนได้วิเคราะห์และแก้ไขปัญหาจากการลงมือทำ การมีความสัมพันธ์ทางวัฒนธรรมเชิงบวกและเข้าใจผู้เรียนที่มีความต่างทางวัฒนธรรม รวมทั้งการจัดสภาพแวดล้อมการเรียนรู้เอื้อต่อการทำงานร่วมกันบนระบบคลาวด์ โดยใช้แอปพลิเคชันเครือข่ายสังคมที่สามารถเข้าถึงแหล่งการเรียนรู้ได้ทุกที่ทุกเวลา Abstract The purpose of this research was to examine the state and needs related to the development of cloud-based flipped classroom using problem-based learning in a multicultural society to enhance critical thinking. Using a questionnaire to collect information from 445 undergraduate students in universities in the Central and Southern regions of Thailand, and employing Snowball Sampling to select samples, using quantitative research methods. The results showed that the majority of the students who responded have moderate knowledge and skill in information and communications technology, and access to the internet via a smart phone. The results of the research into the state and needs reveal that the students require pre-test and post-test assessment. Additionally, their teachers to pay attention to them and provide reinforcement in class, as well as accommodation of cultural diversity among class members. In terms of learning activities, problem-based learning, which gives opportunities to students to analyses and find solutions through practice, is a preferred method. The learning context supports cloud based collaborative work and uses social network applications in learning activities, allowing the class to develop positive cultural relationships that involve learning and understanding about cultural differences among students. Furthermore, students can access learning resources anywhere, and anytime.